Sosialisasi pendaftaran Coretax pada CV. Pustaka Bengawan - Kustyana, Nurulinda Ekwi; Pratiwi, Desy Nur; Pravasani, Yuwita Ariessa (Nur Science Institute, 2025)
Pustaka Bengawan is a micro, small, and medium enterprise (MSME) operating in the publishing and printing sector, and is required to comply with the latest digital tax system, Coretax. However, the company faces limitations in information, understanding, and readiness to effectively access and implement the system. This community engagement initiative aimed to enhance awareness and understanding of Coretax through an interactive workshop and practical demonstration involving the business owner and employees. The materials were delivered in a simple and accessible manner to accommodate participants’ diverse backgrounds. Live demonstrations covered the registration process and tax reporting using Coretax, followed by a Q&A session to address participant concerns. The results showed a significant improvement: participants with a high level of understanding increased from one to four, while those with a low level of understanding decreased from three to one. Key challenges included limited time and varied digital literacy. To address this, supplementary materials, including handouts and video tutorials, were provided. This activity proved beneficial in promoting tax compliance and strengthening communication between taxpayers and the tax authority.